-15+1=-2(x+5)

Simple and best practice solution for -15+1=-2(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15+1=-2(x+5) equation:



-15+1=-2(x+5)
We move all terms to the left:
-15+1-(-2(x+5))=0
We add all the numbers together, and all the variables
-(-2(x+5))-14=0
We calculate terms in parentheses: -(-2(x+5)), so:
-2(x+5)
We multiply parentheses
-2x-10
Back to the equation:
-(-2x-10)
We get rid of parentheses
2x+10-14=0
We add all the numbers together, and all the variables
2x-4=0
We move all terms containing x to the left, all other terms to the right
2x=4
x=4/2
x=2

See similar equations:

| 5x+15=4x-30 | | 6y+54=180 | | -7v+40=-2(v+5) | | -9+3x=+3x+4 | | -2(n+1)=6 | | 9y+y-10y+3y+2y=20 | | 4e-19=-3(e+40 | | 0.3x+1.6=0.8x-2.4 | | 29=c | | -8x-172=44-14x | | -4x+12=4-4x | | 11+3x=3x-2(7-2x) | | 4b+5b+4b+5b=360 | | -18-6k=6(1+3,k) | | 6+2(x-5)+4x=45 | | 3(x-6)-6x=-15 | | 6g+-9g=-3 | | 10=1/3n | | 9×27+2×31=n | | -4x(x-3)=12-4x | | 1/2(28+2x)=5(x-2) | | 23=5+2x | | 3x-1+x=5x-5 | | |2x+4|=6x-4 | | x^2-3x=x+96 | | 3x+15=2x+60 | | (7/9y)+7=(-2/9)y | | 6(x-2)/2=6(x+3)/12 | | 75–3.5y–4y=4y+6= | | 5x-5=3x-1+x | | 1=0.3x-0.6-23 | | -13+x=5x |

Equations solver categories